MID-LIFE CRISIS PEREMPUAN URBAN : ANALISIS FENOMENA SERTA FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Siti Komariah; Dinda Az Zahra; Puspita Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problems of contemporary urban society are closely intertwined with modernization and the double burden borne by middle-aged women. This study aims to analyze the manifestation of the mid-life crisis phenomenon experienced by urban women and identify the structural, economic, and psychosocial factors that influence the occurrence of the crisis in urban areas. The methodology used in this study is a qualitative approach with a literature study method. Data analysis was carried out systematically through gathering academic references, data reduction, data presentation, and drawing conclusions based on the theoretical link between mid-life crisis and urban dynamics. The results show that mid-life crisis in urban women manifests in the form of deep emotional exhaustion, decreased resilience capacity, psychological stagnation, and a subjective critical evaluation of past achievements. This phenomenon is sociologically triggered by an accumulation of structural factors in the form of a double burden between public and domestic roles, the position as a sandwich generation, urban economic uncertainty, and symbolic pressure from social media exposure that constructs unrealistic standards of living and domestic relations. Successfully navigating this critical window is determined by the ability of self-regulatory adaptation to avoid chronic affective disorders in old age.